Tahap Penggunaan Sistem Bangunan Berindustri (Ibs); Konkrit Pratuang Dalam Industri Binaan Serta Impak Terhadap Kos - Nordin, Mohd Taufik (Universiti Sains Malaysia, 2007)
IBS may be defined as building systems in which structural components are manufactured in a factory, on or of site, transported and assembled into a complete structure with a minimal additional site works. Pre-cast concrete is a part of IBS that emphasizes safety in its practice. Nevertheless, usage of Pre-cast concrete in Penang building industry is still very low if compared to the conventional methods because of easy in getting labour supply and low fees. Therefore, a research had been conducted to study the problems faced when using pre-cast concrete, the analysis of pre-cast concrete in buildings constructions in the aspect of its usage frequency, cost effect and benefits. The research is done in Penang, A set of 50 questionnaires were distributed to contractors and 18 had corresponded positively.